A hybrid Protection Scheme based on Deep Reinforcement Learning - Kordowich, Georg; Jaworski, Michael; Lorz, Tobias; Scheibe, Christian; Jäger, Johann (2022 IEEE PES Innovative Smart Grid Technologies Conference Europe (ISGT-Europe), 2022)
The growth of distributed renewable energy re-sources pushes classic protection schemes to their limits. An automated workflow is necessary to handle the volatility of future power systems characterized by constantly changing network states. Therefore a hybrid, deep reinforcement learning based protection scheme is proposed in this paper, which combines a single agent training for central protection with a multi agent training for a decentralized fallback.For this purpose, a training framework using a combination of PowerFactory and Python-Scripts connected via a Shared Memory is developed. The framework is used to train agents using Deep Recurrent Q-Learning. First a central protection is trained, which can then be imitated by decentral agents using only local measurements. Tests of the setup show a fast and selective response, which proves that deep reinforcement learning can indeed automatically generate a protection scheme fulfilling high requirements of dependability and security.<br

Distance Protection Algorithm based on alpha/beta/0-components and Delta Quantities for Getting Insensitive against Power Swings - Jaworski, Michael; Jäger, Johann; Lorz, Tobias (The 15th IET International Conference on Developments in Power System Protection, 2020)
The stabilisation of the distance protection function against inappropriate trip responses due to power swings represents the main topic of this paper. In today's power grids, this problem is covered by the implementation of power swing blocking functions. However, this function is only a corrective add-on algorithm and not an integral part of the distance function itself. This leads to the fact, that symmetrical short-circuits followed up by a power swing are subjected to strongly reduced backup protection dependability from the upstream distance relays. The aim of creating a distance algorithm, which offers inherent power swing insensitivity instead of using a power swing blocking function, is achieved by applying the Δ-quantities of the αβ0-components of voltage and current. Beginning with the basics of the proposed distance algorithm up to a suitable relay logic, the all-important parts of the Δ21 relay are provided and discussed in this paper. Finally, a study case provides the platform for its performance evaluation.<br
Keywords: delta quantities; distance protection; Power swing; power system restoration; αβ0-components

Erdschlusserkennung basierend auf Künstlichen Neuronalen Netzen - Kordowich, Georg; Lorz, Tobias; Jaworski, Michael; Klumpp, Philipp; Perez Toro, Paula Andrea; Gaube, Sven; Kereit, Matthias; Böhme, Klaus; Nöth, Elmar; Jäger, Johann (12. VDE ETG-/FNN-Tutorial Schutz- und Leittechnik, 2022)
Erdschlüsse gehören zu den häufigsten Fehlern im Mittelspannungsnetz. Gleichzeitig ist insbesondere die Erkennung von hochohmigen Erdschlüssen eine der schwierigsten Aufgaben der Schutztechnik. Durch die zahlreichen Einflussparameter wie beispielsweise Fehlerursache, Bodenbeschaffenheit und Witterung auf Fehler- und Erdimpedanz können konventionelle Verfahren Erdschlüsse nicht in jedem Fall zuverlässig erkennen. In diesem Poster soll deshalb ein Konzept vorgestellt werden, das durch Verwendung von Künstlichen Neuronalen Netzen eine Ergänzung zu den etablierten Verfahren bilden soll. Durch ein Training sollen die Neuronalen Netze erlernen die komplexen Muster der Erdschlüsse zu erkennen und von anderen Schalthandlungen oder Fehlern abgrenzen können. Im Gegensatz zu konventionellen Schutzkonzepten, deren Erkennung meist von den Werten einzelner Parametern abhängt, sollen die Neuronalen Netze ein generisches Verständnis für die Muster entwickeln und so robuster und vielseitiger einsetzbar sein. Für die Generierung der Trainingsdaten ist ein möglichst akkurates Modell des entsprechenden Einsatzgebietes nötig. Mit diesem können automatisiert Simulationen durchgeführt, und Messdaten exportiert werden. Dabei werden verschiedene Fehlerorte und -zeitpunkte mit verschiedenen Parametern simuliert, um einen möglichst diversen Datensatz für ein robustes Training zu generieren. Die Messdaten aus den Simulationen werden anschließend für das Training der Neuronalen Netze verwendet. Um die Fehlererkennungsfähigkeit der Netze zu verifizieren, können diese anschließend mit Messdaten aus realen elektrischen Netzen validiert werde

Hybrid fuzzy evaluation algorithm for power system protection security assessment - Meyer, Georg Janick; Lorz, Tobias; Wehner, Rene; Jäger, Johann; Dauer, Maximilian; Krebs, Rainer (Electric Power Systems Research, 2020)
System Protection Security Assessment is an important task in modern energy grids to ensure system security at all. The assessment system is particularly challenged by multivariate grid structures caused by volatile renewable infeeds. This paper presents an innovative strategy to evaluate the protection relay coordination of system-wide power grids. A way to calculate the quality of all protection relays based on realistic simulation data and independent of the protection method was sought. The hybrid algorithm consists of two major steps. First, a systematic analysis with various fault simulations is performed and the measurement results of all relays of all simulations are used as database. Subsequently, the use of fuzzy sets allows to express the quality of each relay setting regardless of its type. Specifically developed for the use of an optimization algorithm, finally, a new protection coordination is determined for an adapted version of the IEEE 9 bus grid. The results are validated, discussed and the effectiveness of the methodology compared to conventional setting rules.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Fuzzy evaluation; Optimization algorithm; Protection coordination; Protection security assessment; Relay settings

Interconnected grid protection systems - reference grid for testing an adaptive protection scheme - Lorz, Tobias; Jäger, Johann; Selimaj, Antigona; Hacker, Immanuel; Ulbig, Andreas; Heckel, Jan Peter; Becker, Christian; Dahlmanns, Markus; Fink, Ina Berenice; Wehrle, Klaus; Erichsen, Gerrit; Schindler, Michael; et al. (27th International Conference on Electricity Distribution (CIRED 2023), 2023)
The German power system is facing a continuous increase of volatile, decentralized power supplies from renewable energies. Growing loads from the mobility sector will increase the strain on the power grids even further. Faced with these rising challenges, current protection systems for distribution grids will likely encounter difficulties to provide the same level of security and dependability as they are often designed for a static grid protection with unidirectional power flow. This paper provides a reference grid for detailed study of protection behaviour based on real-world challenges encountered by German distribution grid operators. The grid consists of a 110kV high-voltage system and a 20kV medium-voltage system, which both are dominated by DER installations and a divergence between generation and load centres. The grid models were developed in close coordination with DSOs and provide a facility to operate in specific scenarios, that could be utilised in future grid operations.
CRIS-Team Scopus Importer:2024-12-16

Interconnected network protection systems - the basis for the reliable and safe operation of distribution grids with a high penetration of renewable energies and electric vehicles - Lorenz, Matthias; Pletzer, Tobias Markus; Schuhmacher, Malte; Sowa, Torsten; Dahms, Michael; Stock, Simon; Babazadeh, Davood; Becker, Christian; Jäger, Johann; Lorz, Tobias; Dahlmanns, Markus; Fink, Ina Berenice; et al. (IET Conference Proceedings, 2022)
Power grids are increasingly faced with the introduction of decentralized, highly volatile power supplies from renewable energies and high loads occurring from e-mobility. However, today's static grid protection cannot manage all upcoming conditions while providing a high level of dependability and security. It forms a bottleneck of a future decarbonizing grid development. In our research project, we develop and verify an adaptive grid protection algorithm. It calculates situation dependent protection parameters for the event of power flow shifts and topology changes caused by volatile power supplies due to the increase of renewable generation and the rapid expansion of e-mobility. As a result the distribution grid can be operated with the optimally adapted protection parameters and functions for changing operating states. To safely adjust the values on protection hardware in the field, i.e., safe from hardware failures and cyberattacks, we research resilient and secure communication concepts for the adaptive and interconnected grid protection system. Finally, we validate our concept and system by demonstrations in the laboratory and field tests.
CRIS-Team Scopus Importer:2024-12-16

System Integrity Protection by Orbital Grid-forming Mode for VSC - Lorz, Tobias; Jaworski, Michael; Jäger, Johann (16th International Conference on Developments in Power System Protection (DPSP 2022), 2022)
The primary challenge is to develop a protective function that utilises a VSC for fulfilling this task of dynamic system stabilization. In consequence, the protection function is realized in form of a converter control scheme that enables the VSC's operation in grid-forming mode (OGM) alongside with the synchronous generator. The Orbital Grid-forming mode OGM offers current limitation without a separate control-loop and even without measuring the current. Furthermore, it enables the VSC to stabilize electromechanical dynamics of synchronous machines by obtaining a maximum angular deviation between its internal voltage and their rotors. This means a generator cannot lose synchronism to the VSC and its rotor experiences a floating anchorpoint, which hinders its acceleration or deceleration until the dynamic excursion of the machine is over.
CRIS-Team Scopus Importer:2024-12-16
Keywords: GRID-FORMING; POWER SYSTEM RESTORATION; ROTOR ANGLE STABILITY; SYSTEM INTEGRITY PROTECTION